The Concentration Of A Near Non-Radiative Magnetic Field By Changing The Angle Of The Spiral Coils On The Substrate - Pokorný, Josef (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2021)
This paper deals with the concentration of a near non-radiative magnetic field using twocoils excited with opposite polarity and offset to each other. This allows variability in the location ofthe receiving coil of the charging element off-center of the transmitting coil. The magnetic inductionradiation was simulated in Maxwell using the eddy current simulation. Therefore, it is only an inductivepower transfer (IPT).
Keywords: Wireless power transfer; Substrate spiral coil; inductive power transfer